Active targeted dual-modal CT/MR imaging of VX2 tumors using PEGylated BaGdF5 nanoparticles conjugated with RGD. (14th June 2018) - Wang, Tao; Jia, Guorong; Cheng, Chao; Wang, Qiuhu; Li, Xiao; Liu, Yanyan; He, Chaofan; Chen, Luguang; Sun, Gaofeng; Zuo, Changjing
Abstract : RGD-PEG-BaGdF5 NPs can be used as CT/MR dual-modality contrast agents of solid tumors via the RGD-mediated tumor vasculature targeting strategy. Abstract : Multimodal imaging can improve the accuracy of cancer diagnosis by combining two or more imaging modalities into one system. In this study, PEGylated BaGdF5 nanoparticles (NPs) were synthesized by a hydrothermal method, and the formed PEG-BaGdF5 NPs showed good X-ray attenuation properties and positive MR contrast effects in vitro . Considering that the overexpression of integrin αv β3 in the endothelial cells of angiogenic tumor vasculature is universal, RGD peptide, which can recognize and bind integrin αv β3 specifically, was connected to the surface of PEG-BaGdF5 NPs. The resulting RGD-PEG-BaGdF5 NPs had good biocompatibility and a long half-life in vivo . In VX2 tumor-bearing mice, the HU values and MR signal enhancement of tumor sites in the targeted group were both higher than that in the non-targeted group after intravenous injection of RGD-PEG-BaGdF5 NPs or PEG-BaGdF5 NPs, respectively. Therefore, the RGD-PEG-BaGdF5 NPs may be used as dual-modal CT/MR contrast agents of different types of solid tumors via an active RGD-mediated vasculature targeting pathway.